Evaluation of Public Perception and Knowledge of Plastic Recycling Technology in the Yogyakarta Special Region, Indonesia - Redhita, Redhita Rizky Shantania Putri; Dhinar, Dhinar Mustika Natalia; Andika, Andika Dwi Saputra (International Conference on Health Sciences, 2026)
The accumulation of waste in Indonesia has been increasing year by year and remains poorly managed. This study evaluates public perception and knowledge of plastic recycling technology to support the implementation of a sustainable circular economy. This study employed a quantitative research approach, categorised as descriptive and verification research, using a survey-based confirmatory model to examine causal relationships among variables through hypothesis testing. Data were collected through random sampling surveys and analysed using the Structural Equation Model (SEM) and Partial Least Squares (PLS) techniques. A total of 63 respondents from the Yogyakarta region participated. The findings show that age, education, and primary occupation variables have loading factor values greater than 0.70. The structural model revealed that R-square was highest for the Public Understanding variable (0.133), followed by the Findings Implication variable (0.093). The significance test (p < 0.05) indicated a positive relationship between public understanding and the implications of the findings (0.305). In conclusion, the Public Understanding variable, which integrates both knowledge and perception, emerges as the most dominant factor among all variables. While this variable is influenced by several surrounding independent factors, the most substantial outcome is its role in driving behavioural change, as reflected in the involvement of all stakeholders in plastic recycling efforts, both manually (3R) and through the use of zero-to-waste technologies.